2019
DOI: 10.12659/aot.917296
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Early Recurrence of Hepatocellular Carcinoma in Patients with Cirrhosis Who Had Received Deceased Donor Liver Transplantation: A Multicenter Study

Abstract: BackgroundEarly recurrence after liver transplantation (LT) is still a clinical problem. This multicenter study evaluated the Milan, Hangzhou, and AFP model-based criteria for prediction of early recurrence of HCC in patients with cirrhosis who had undergone LT.Material/MethodsFrom the China Liver Transplant Registry (CLTR) database, we analyzed data of 589 HCC patients who had undergone LT between Jan 2015 and Jan 2019. Imaging data and AFP levels were evaluated immediately before LT. Recurrence and overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Fifty-eight studies that compared the Milan criteria with other criteria were included in the study. Of these, 41 studies compared the Milan and UCSF criteria 33–45 , 47–51 , 53 , 55–60 , 63 , 64 , 67 , 68 , 70–73 , 76–79 , 83 , 85 , 86 , 90 , 16 studies compared the Milan and UPTS criteria 46 , 52 , 54 , 59 , 61 , 62 , 65 , 66 , 68 , 73 , 74 , 78 , 83 , 84 , 86 , 87 , seven studies compared the Milan and AFP criteria 69 , 75 , 80–82 , 87 , 88 , four studies compared the Milan and MT2 criteria 82 , 87–89 , one study compared the UPTS and MT2 criteria 87 , one study compared the UPTS and AFP criteria 87 , three studies compared the MT2 and AFP criteria 82 , 87 , 88 , and six studies compared the UCSF and UPTS criteria 59 , 68 , 73 , 78 , 83 , 86 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-eight studies that compared the Milan criteria with other criteria were included in the study. Of these, 41 studies compared the Milan and UCSF criteria 33–45 , 47–51 , 53 , 55–60 , 63 , 64 , 67 , 68 , 70–73 , 76–79 , 83 , 85 , 86 , 90 , 16 studies compared the Milan and UPTS criteria 46 , 52 , 54 , 59 , 61 , 62 , 65 , 66 , 68 , 73 , 74 , 78 , 83 , 84 , 86 , 87 , seven studies compared the Milan and AFP criteria 69 , 75 , 80–82 , 87 , 88 , four studies compared the Milan and MT2 criteria 82 , 87–89 , one study compared the UPTS and MT2 criteria 87 , one study compared the UPTS and AFP criteria 87 , three studies compared the MT2 and AFP criteria 82 , 87 , 88 , and six studies compared the UCSF and UPTS criteria 59 , 68 , 73 , 78 , 83 , 86 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in a recent study, patients with HCC selected for transplantation based on the AFP model had equal or worse overall survival and higher risk of recurrence than those patients selected with the Milan, UPTS, and MT2 criteria 87 . In another study, the AFP model identified patients with HCC who fulfilled the Milan criteria and who had a low or high risk of tumour recurrence, but it was not able to do the same for patients who exceeded the Milan criteria 80 . In the study by Grąt et al ., patients who did not meet the Milan criteria but did meet the AFP criteria had a 74.1 per cent 5-year recurrence-free survival rate, which was inferior to the recurrence-free survival of patients who met the Milan criteria ( P = 0.045).…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent publications, the best tumor-free 2-year survival was achieved in patients who underwent LT for HCC within the Milan criteria. The recurrence rate (RR) in the cohort comprising 589 patients published by Al-Ameri et al [38] was 8.9% within 2 years; however, in patients within the AFP model or within the Hangzhou criteria, the RR is higher with 11.8 and 15.8%, respectively. The best 5-year tumor-free survival was achieved in a total of 965 analyzed patients if they were within the 5-5-500 rule or within the Milan criteria with a low RR of only 7.3 and 7.5%, respectively [19].…”
Section: Resultsmentioning
confidence: 99%
“…Most recent data published show a 5-year OS of 82.5% [15] (Table 1) comparable to the expected survival of patients who do not have HCC. Most importantly with the modern diagnostic imaging and perioperative management even in patients with expanded Milan criteria, that is, the Hangzhou criteria [38], 5-5-500 rule [19], UCFS [17], AFP model [16], TTV-AFP model (for beyond Milan patients) [16], Kyoto criteria [16], and UT7 criteria [15], an acceptable outcome is obtained (Table 1). Further, the MoRAL score is an excellent predictor for HCC recurrence after LT [16] (Table 1).…”
Section: Discussion/conclusionmentioning
confidence: 99%